Pengaruh Proporsi Terigu dan Puree Sukun (Artocarpus Communis) terhadap Sifat Organoleptik Roti Tawar - Amajida, Melinda Khansa; Astuti, Nugrahani; Bahar, Asrul; Widagdo, Andika Kuncoro (VISA: Journal of Vision and Ideas, 2025)
This study aims to determine the effect of the proportion of flour, breadfruit puree and liquid on the organoleptic properties of white bread and to determine the best nutritional content of white bread based on the results of organoleptic tests. This type of research is an experimental study with a single-way design, namely the independent variables include the proportion of breadfruit puree 30%, 40% and 50% and flour 70%, 60% and 50%. The data collection technique uses observation techniques, with questionnaire instruments assessed by 20 trained panelists, namely lecturers of S1 Culinary Education and S1 Food Technology. Data analysis used is Kruskal Wallis and Mann-Whitney further test to find the best results from the organoleptic test of bread puree bread. The best results are then tested chemically in the laboratory of the Industrial Research and Consultation Center (BPKI). The results showed that 1) Substitution of breadfruit puree, flour and liquid affected the outer color criteria, but did not affect the shape and texture of the outer part. And also affects the texture of the bread, but does not affect the color, pores, aroma and taste of the inside of the sandwich bread, and 2) the results of chemical tests on the nutritional content of the best bread, namely with 50% breadfruit puree substitution and 50% flour with nutritional content including 48.29 g carbohydrates, 8.89 g protein, 2.39 g fat, 3.11 g fiber, 36.60 g water, 18.65 mg calcium, 9.05 mg vitamin C.